1999
DOI: 10.1111/j.1746-1561.1999.tb04169.x
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Survey of Financing Health‐Related Services for Special Education Students

Abstract: The Individuals with Disability Education Act (IDEA) requires state educational systems to provide school-based, health related services (RS). This survey determined the financing arrangements used by states for health-related services for school-aged children with disabilities. A survey was sent to directors of special education, Medicaid, and public health departments in each of the 50 states. Financial patterns for RS were sought at the state level for children ages 3-21 with disabilities for the 1993-1994 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…2 Also, on the basis of a national survey on Medicaid financing of health services for special education students, Rodman et al report that in 1993-1994 only 8 states had established a Medicaid financing mechanism with almost all of their school districts, while 21 states had a mechanism with some or most schools districts, and the remainder of states did not have any Medicaid financing of schoolbased health care. 4 The same survey results suggest that the process a school district must follow to become an eligible Medicaid provider is lengthy and complex, typically requires the establishment of an interagency agreement with the state Medicaid agency, and requires commitment of resources by the school district to administer the program. These logistical difficulties may explain why more school districts do not take advantage of Medicaid as a source of funding for health services.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…2 Also, on the basis of a national survey on Medicaid financing of health services for special education students, Rodman et al report that in 1993-1994 only 8 states had established a Medicaid financing mechanism with almost all of their school districts, while 21 states had a mechanism with some or most schools districts, and the remainder of states did not have any Medicaid financing of schoolbased health care. 4 The same survey results suggest that the process a school district must follow to become an eligible Medicaid provider is lengthy and complex, typically requires the establishment of an interagency agreement with the state Medicaid agency, and requires commitment of resources by the school district to administer the program. These logistical difficulties may explain why more school districts do not take advantage of Medicaid as a source of funding for health services.…”
Section: Discussionmentioning
confidence: 79%
“…1-3 Also, many schools are expanding students' access to mental health services through interagency agreements with state Medicaid agencies or through other sources of public and private funding. 4 Factors in this trend may be greater awareness of the high level of unmet need for mental health care among school-aged children, 20% of whom have a psychiatric disorder, 5 and concern over barriers in access to mental health services among low-income children and children from racial and ethnic minority backgrounds. [6][7][8] Another factor is the estimated 3 million special education students who have a mental disorder9; under the 1975 Education for All Handicapped Children Act school districts are required to provide access to mental health services whenever mental health treatment is part of a student's individual education plan or IEP.…”
Section: Introductionmentioning
confidence: 99%
“…As hypothesized, counties in the highest quartile of per-student education spending had lower prevalence, suggesting the substitution of education and Medicaid-reimbursed services. Because the needs of children with ASD cross the boundary between education and healthcare, counties with fewer education resources may turn to Medicaid to pay for their services (Koppelman 2004; Noel and Shreve 2006; Parrish et al 2004; Rodman et al 1999). Counties with more students and those with a greater proportion of students receiving special education services (both measures of potential system stressors) tended to have greater Medicaid-enrolled prevalence, adding some evidence to this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…While little data are available on the educational costs associated with these children, a report commissioned by the Government Accountability Office found that the average annual expenditure during the 1999–2000 academic year for children with autism was $18,000, almost three times that of children not in special education, and the second highest average expenditure among all special education categories (Chambers et al 2004). These services often include specialized classrooms, one-on-one instruction, intensive behavioral interventions (Lord et al 1989), and speech, language and occupational therapy, for children to receive an education in the least restrictive environment appropriate to their individual needs (Koppelman 2004; Noel and Shreve 2006; Parrish et al 2004; Rodman et al 1999). …”
Section: Introductionmentioning
confidence: 99%
“…32 School nurses focus primarily on tracheostomy management, ventilator monitoring, tube feeding, temperature control, catherization, and seizure management. 23 33 The management of injuries is an area for further development but will require collective efforts among nurses, teachers, aides, administrators, and parents.…”
Section: Implications For Preventionmentioning
confidence: 99%